PENGUJIAN TURBIN AIR PUSARAN GRAVITASI DENGAN VARIASI OVERLAP RATIO ROTOR DAN PENGGUNAAN ENDPLATE - Muhammad Luthfi; Meri Rahmi; Rachmatullah Rachmatullah (Jurnal Teknologi Terapan, 2022)
The gravitational water vortex turbine is a turbine system that can convert the energy from artificial water vortex by means of the drained water through the basin outlet to the kinetic energy of rotor rotation Many researches were conducted to improve the efficiency of this turbine by changing the shape of basin, or the rotor. Meanwhile, the Savonius rotor has good starting rotation and ease of fabrication, but low efficiency. One way to increase the efficiency of this rotor is to apply the gap between the blades which is called Overlap Ratio (OR). In this research, the gravitational water vortex turbine with the conical-shape basin was combined with the various-OR Savonius rotors with area proportion of 26,88% and without endplate and the effect was observed to the efficiency of turbine. This research aims to study the effect of various OR values and use of endplate of Savonius rotor to the efficiency of Gravitational Water Vortex Turbine System. The volume flowrate of channel was maintained constant at 0,005 m3/s. The result showed that for all rotors, the greater efficiency occurred in the low rotational speed. Moreover, the rotor with OR of 0,15 had greater mechanical efficiency which was around 22,78% for the rotor with endplate 26,88% and 27,18% for the rotor without endplate than rotor with OR of 0. Meanwhile, rotor without endplate had higher maximum mechanical efficiency for all OR variation than that with endplate 26,88%.